PERAN BAPPEDA DAN PARTISIPASI MASYARAKAT DALAM IMPLEMENTASI PEMBANGUNAN SANITASI DI DESA JAMBU KABUPATEN SEMARANG. - Andre, Rahardian; Santosa, Edi; Astuti, Puji (Journal of Politic and Government Studies, 2017)
This research conducted to explain the result from the role of Badan Perencanaan Pembangunan Daerah (BAPPEDA) Semarang Regency and participation of society in sanitation development implementation in Jambu Village, Semarang Regency. The purposes of the research are society welfare enhancement through a planned effort, do an evaluation of accountable region development plan, do an assesment of region development potential analyticaly, do coordination of integrated planning, and do administration BAPPEDA Semarang Regency. This research is helpful for monitoring and evaluating implementation of sanitation development plan in Jambu Village including to assure policy, program, and project are implemented accordance with the determinded plan, and also to obtain feedback from policy, program, and project that is done as well as in progress. This research used qualitative descriptive method which supported by quantitative data and particularly used mix method research focused on purposive sampling technique to explain the role of BAPPEDA and participation of society in sanitation development implementation. Source of data were primary and secondary data. Collection of the data used observation, interview, and literature review. The result shows that implementation of sanitation development in Jambu Village Semarang Regency has worked well. The positive effect of this policy has achieved proved by society utilize irrigation canal easily for daily life, perceive ‘gotong-royong’ to other society, and easily get clean water so they have assured health and well field watering. The exist of sanitation development program in Jambu Village is expected affect to better social-economic and physic condition for society thus farmer’s income will increase. Key words: village development, sanitation development, society’s participation, and the role of BAPPEDA